Pacing demands in competitive Nordic skiing - Losnegard, T.; Kocbach, J.; Sandbakk, Ø. (International Journal of Sports Physiology and Performance, 2025)
Background and Purpose Cross-country skiing, biathlon, and Nordic combined are Winter Olympics sports that involve cross-country skiing in undulating terrain, characterized by various subtechniques and repeated intensity fluctuations. The stochastic interval profile of these sports necessitates the continuous regulation of work and energy expenditure throughout training sessions and competitions, a concept known as pacing. With the advent of technological advancements that allow for the measurement of these features during training and competitions, scientific studies have broadened our understanding of the associated racing and pacing demands. We provide the current scientific overview of pacing demands in competitive cross-country skiing, biathlon, and Nordic combined and propose guidelines for how performance can be enhanced by adjusting pacing behavior.